The reality of the health system in Iraq (challenges and levels) - Noura Nouri Abdoun, Asst. Lect.; Salam Abdel Ali Al- Abadi , Prof. Dr. (lark, 2025)
Iraq has suffered over the past decades from a continuous decline in the health situation, and its health system has witnessed a major defect since the middle of the last century due to successive wars and an economic blockade that lasted for more than twelve years, as well as the American occupation of Iraq in the year (2003) and political and economic instability And administrative and financial corruption, which contributed greatly to the deterioration and noticeable decline in the level of health and medical services in the absence of political will and strategic vision to advance the reality of this important and vital sector within the comprehensive development system The reality of health services in Iraq is weak in terms of logistical or instrumental services and does not correspond to the momentum in medical services. Therefore, we find that the indicator of the deficit in providing health services is very high, as health centers and hospitals are not sufficient to meet the needs of people in this aspect, not to mention the loss The simplest types of medical services that these centers and hospitals are supposed to provide to their beneficiaries. The research aims to know the reality of the health system in Iraq. And revealing the levels of the health system in Iraq and identifying the threats to the health system in Iraq. Among the most prominent findings of the research is the existence of awareness by individuals to follow healthy eating habits in food. Individuals are not keen to follow up on regular medical examinations.